Studi Efektivitas Pemanfaatan Sarana Lingkungan Pada Pusat-Pusat Pelayanan Satuan Wilayah Pengembangan (SWP) III Kabupaten Semarang - Pramudita, Yustinus Bima (Magister Pembangunan Wilayah dan Kota,Undip, 2017)
The Region Development UnitÂ (SWP) III with Tengaran and Suruh subdistrict service center being in the south of Semarang District. The long distance to reach the capital of Semarang district in northern, geographically less favorable for the south. It assumpted SWP III more served by others. Based on the fact above, it is important toÂ study the effectiveness of neighborhood facilities service in SWPÂ III Semarang District. Object research includes seven neighborhood facilities according to SNI 03-1733-2004 namely government and public services, education, health, religion, trade, culture, and open space facilities. This research using the quantitative analysis with the scoring method. Variables observed in this study covering the availability, accessibility, the intensity of the use of facilities. Data collection with a questionnaire, interview, observation, and document review. Sample methods used is simple random sampling and purpossive sampling. The result of this research are (1) four neighborhood facilities categories effective are religion facilities, health, the government and public service, and education, while three having effective enough are the trade facilities, culture, and open space. (2) Tengaran and Suruh Subdistrict not capable of being service center for SWP III.